Social Competence of Minority Muslims: : Expression and Articulation of Chinese Muslim Identity in Surabaya - Winarto Eka Wahyudi (ADP Publisher, 2023)
This study explores the social competence of the Chinese Muslim minority community in Surabaya, focusing on the expression and articulation of their identity within a diverse societal context. The background of the research lies in the unique dynamics faced by this minority group in navigating their religious and cultural identity amid a predominantly non-Chinese and non-Muslim environment. The research investigates the modes of expression employed by Chinese Muslims to manifest their identity and the challenges they encounter in articulating their distinct cultural blend. Utilizing a sociological perspective, the study employs qualitative research methods, including in-depth interviews and content analysis of relevant materials. The findings illuminate the multifaceted aspects of social competence exhibited by the Chinese Muslim community, encompassing effective engagement, cultural preservation, and social integration strategies. Notably, the study reveals the community's commitment to upholding social norms, steering clear of practical politics, and actively contributing to societal harmony. The research contributes to the broader discourse on religious and cultural diversity, offering insights for policymakers and community leaders seeking to foster inclusivity in multicultural societies.